KEMAMPUAN MENGUBAH TEKS WAWANCARA DALAM BENTUK NARASI - Reski Amalia; Suhartini Khalik; M Nurzin R. Kasau (Program Studi Pendidikan Bahasa Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Sidenreng Rappang, 2021)
These findings aim to obtain complete data and information about the ability to change the interview text in narrative form. The total student population was 76 students divided into three classes, while the sample was the total sample. The techniques used in data collection are documentation techniques and test techniques. The instrument used was in the form of an interview text which then the students were assigned to convert it into a narrative form. From the research results, it can be seen that students who get a score of 65 and above are 31 students (40.79%) and students who get a score of less than 65 are 45 students (59.21%). Based on the predetermined qualification standards, namely students who get a score of 65 and above at least 85%, it can be concluded that students have not been able to change the interview text into a narrative form. because it does not reach the predetermined qualification standards.